Transforming Borneo from land exploitation to sustainable development - Goh, Chun Sheng; Potter, Lesley (ISEAS-Yusof Ishak Institute, 2024)
'There is an energizing boldness in this synthesis: the right big-picture questions aligning all the way down to the right complexities on the ground, and across the diverse territories that comprise contemporary Borneo. A manifesto for the kinds of cross-sectoral and applied research that can make the difference to the future of Borneo.' - Cynthia Ong, Chief Executive Facilitator, Forever Sabah 'A surgical and timely compendium on the transformation of Borneo's forests and land use with clear regional implications. If you care about the future of conservation in this part of the world, you will find all the key ingredients here for its salvation.' - Gopalasamy Reuben Clements, Professor at Sunway University, Co-founder of Nature-Based Solutions 'A perspective about balancing the future amidst the need for economic and social development while providing a better and more sustainable Borneo. It is something that you will need to help drive home change and make a sustainable impact for people and planet without compromising profit.' - Timothy Ong, Head of Circular Bio-economy Unit, Malaysian Investment Development Authority (MIDA)
Title from publisher's bibliographic system (viewed on 27 Feb 2024)
Keywords: Sustainable development / Borneo; Economic development / Borneo; Land use / Borneo; Agriculture / Economic aspects / Borneo